Pengaruh Program Pengungkapan Sukarela (PPS), Sosialisasi Perpajakan Dan Kesadaran Pajak Terhadap Peningkatan Kepatuhan Wajib Pajak Orang Pribadi (Survey Pada Persepsi Konsultan Pajak Anggota Ikatan Konsultan Pajak Indonesia (IKPI) Cabang Bogor) - Siti Nurazizah; Muhammad Dahlan (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the effect of the Voluntary Disclosure Program (PPS), Tax Socialization and Tax Awareness on increasing individual taxpayer compliance based on the perception of tax consultants who are members of the Indonesian Tax Consultant Association (IKPI) Bogor branch. This study uses a quantitative approach with a data collection method through distributing questionnaires. The sample was determined by purposive sampling with a total of 60 respondents. The data analysis technique used was multiple linear regression with the help of the SPSS version 26 program. The results of the study indicate that partially, the Voluntary Disclosure Program and Tax Awareness have a positive and significant effect on increasing individual taxpayer compliance, while Tax Socialization has a positive but insignificant effect. Simultaneously, the three variables have a positive and significant effect on increasing individual taxpayer compliance.